Motor control and learning : a behavioral emphasis - Schmidt, Richard A. , 1941-; Lee, Timothy Donald , 1955- (Human Kinetics, 2011)
"Motor Control and Learning, Fifth Edition, begins with an introduction to research and fundamental concepts important to understanding motor behavior. In the second part of the text, readers will learn about motor control, including contributions from the sensory and central nervous systems; principles related to speed and accuracy; factors involved in movement control and coordination; and factors that determine skill differences between people and among groups of people. The final portion of the text covers skill acquisition, examining special methodological problems for studying motor learning, various theoretical treatments of motor learning, and factors associated with the retention and transfer of skills."--pub. desc